ПСИХОЛОГІЧНА ДІЯЛЬНІСТЬ СУДУ ПРИСЯЖНИХ У НАРАДЧІЙ КІМНАТІ - Шувальська, Люсьєна Романівна (SUPREMANCE OF LAW, 2017)
The author examines the work of the jury-judges in the deliberation room, which flows in a specific psychological relations arising between them. It describes the compliance rules of legal procedure and the establishment of psychological communication between the jury-judges in the deliberation room, as a guarantee of a fair trial taking decisions and ensuring the independence of the external influences on the process of adoption in criminal proceedings. Analyzes the inner conviction and a legal consciousness, as the main psychological factors that influence the decision to the jury-judges.
Keywords: jury; deliberative room; judgment; the inner conviction; a legal consciousness